Pastoral Konseling Pasien Skizofrenia: Pastoral Konseling Pasien Skizofrenia - Suwito, Tri Prapto; Nidin, Solihin Bin; Ginting, Jamsen (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
People with schizophrenia often experience thoughts that deviate from reality, unreal thoughts related to psychological disorders, thought disorders, and behavior changes. This condition can cause sufferers to have trouble recognizing between reality and their possess considerations. Schizophrenia may be a combination of life's chaos and stress as well as signs of changes in well-being. Its characteristics include: abnormal perception in the form of hallucinations; distorted judgments of thoughts that result in extraordinary beliefs and delusions; distorted mind constructions that manifest as language disorders; unusual and often limited emotions, hedonia, and willpower; widespread cognitive problems, particularly those affecting memory and executive function; a seemingly strange behavior that can only be explained in the context of these unusual experiences and distorted control systems; It seems increasingly clear that there is a motor and developmental dimension. Schizophrenia can appear differently which is quite a collection; No two cases are exactly the same. Symptoms of schizophrenia do not often occur before a person reaches puberty, occurring more often in the adult half-life. Schizophrenia is a chronic and complicated mental disorder that has a great impact on thoughts, perspectives, and actions. somebody. This disorder is a mental disorder characterized by the presence of symptoms such as hallucinations, delusions, thinking disorders, behavioral disorders, and emotional disorders, so this disorder can affect a person's ability to think logically, feel appropriate emotions, and behave normally. Schizophrenic disorder can vary from person to person, generally including hallucinations such as thinking in unreal dreams by hearing and seeing them in the mind. Hallucinations can be sounds, visions, or other sensations that are not based on reality. Schizophrenic patients also have beliefs that are not based on reality or referred to as delusions where the patient may have the belief that they are being stalked, pursued, or threatened by others. In addition, there are difficulties in organizing thoughts and speaking logically. Thinking disorders can be in the form of difficulty in expressing thoughts, difficulty in understanding abstract concepts, or difficulty in making decisions, this can lead to aggressive behavior, uncontrollable behavior, or behavior that does not conform to social norms, as well as difficulty in regulating emotions, such as feeling sad or angry for no apparent reason.